2009
DOI: 10.1590/s0102-67202009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Partial gastrectomy associated to anterior truncal vagotomy: alterations in metabolism of the calcium. Experimental study in rats

Abstract: BACKGROUND: The calcium is not absorbed in the lack of hydrochloric acid and the osteomalacia and osteoporosis may occurs; it is well recognized in patients that had gastric resection. AIM: To evaluate the effects of the partial gastrectomy associated to anterior truncal vagotomy in the absorption and metabolism of calcium. METHODS: Eighteen adults male Wistar rats were submitted to partial gastrectomy associated to anterior truncal vagotomy (GXT, eight animals) and the sham operation (10 animals, control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…After the gastric resection the content of calcium in the bone is reduced and became more pronounced during the time 12 . These results were observed in other studies 5,1,12,16,17 . Patients submitted to bariatric surgery present micronutrient deficiencies of vitamin B12, iron, calcium, and vitamin D, and nutrient and mineral supplementation are essential for the treatment and prevention of nutritional and metabolic complications 8 .…”
Section: Discussionsupporting
confidence: 89%
“…After the gastric resection the content of calcium in the bone is reduced and became more pronounced during the time 12 . These results were observed in other studies 5,1,12,16,17 . Patients submitted to bariatric surgery present micronutrient deficiencies of vitamin B12, iron, calcium, and vitamin D, and nutrient and mineral supplementation are essential for the treatment and prevention of nutritional and metabolic complications 8 .…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies showed that the partial gastrectomy associated to anterior truncal vagotomy were a good experimental model to study the iron metabolism 21 and calcium metabolism 22 . However, the etiology of iron malabsorption after gastrectomy has not been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…This fact added to the reduced gastric capacity and the absence hydrochloric acid increases the iron and other nutrients deficiencies 15 . Previous studies showed that the partial gastrectomy associated to anterior truncal vagotomy were a good experimental model to study the iron metabolism 27 and calcium metabolism 28 .…”
Section: Fecal Iron and Apparent Iron Absorptionmentioning
confidence: 99%